To solve a quadratic equation, we can use the ___ formula. A. linear B. quadratic C. cubic D. exponential 相关知识点: 试题来源: 解析 B。解二次方程可以用二次公式,quadratic 是二次的;linear 是线性的;cubic 是三次的;exponential 是指数的。反馈 收藏 ...
Solve the following quadratic equation using quadratic formula: a(x2+1)=x(a2+1) View Solution Q2 Solve the given quadratic equation by using the formula method, a(x2+1)=x(a2+1) View Solution Q3 Solve the following quadratic equation by factorization :a(x2+1)−x(a2+1)=0 View ...
解析 You getx= (-b± √ (b^2-4ac))(2a)= (-(5)±√ ((5)^2-4(1)(-3)))(2(1))= (-5± √ (37))2=- 52± (√ (37))2The solution of the equation x^2+5x-3=0 is x such thatx=- 52± (√ (37))2.反馈 收藏 ...
-3;-2;-5;-7;3 x^2+6x+9=0: 解:x=-3 x^2+7x+10=0: 解:x=-2, x=-5 x^2+4x-21=0: 解:x=-7, x=3反馈 收藏
A quadratic equation is of the form ax2 + bx + c = 0 where a ≠ 0. A quadratic equation can be solved by using the quadratic formula. You can also use Excel's Goal Seek feature to solve a quadratic equation.
An equation like ax² + bx + c = 0, can be solved by using the quadratic equation formula: x =-b ±√b² - 4ac2a or x =-b ±√Δ2a Where Δ(Delta)= b² - 4ac See step-by-step solution below: Identify the coefficients ...
Instead of solving a quadratic equation by completing the squares (shown in Algebra 1) we could solve any quadratic equation by using the quadratic formula.A quadratic equation with real or complex coefficients has two solutions, called roots. These two solutions may or may not be distinct, and...
Fast and easy way to calculate Quadratic Equation online by using formula. Make a calculation right now!
Although it looks hard, this formula is one of the two most memorable ones in mathematics. Since it has to apply to any quadratic equation we must represent the numerical parts of the three terms by letters, using a, b, and c: $$a{x^2} + bx + c = 0$$ (1) You will agree ...
Quadratic Formula: The quadratic formula is a formula that is applied to determine the roots of any quadratic equation whose standard form is {eq}ax^2+bx+c=0 {/eq}. It is given by the formula {eq}x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a} {/eq}. Answer and Explanation...